Metatarsophalangeal prosthesis for hallux rigidus. Review of current models and CartivaTM interposition endorthesis - Nuñez-Samper, Mariano; Viladot-Pericé (In Memoriam), Ramón (Journal of the Foot & Ankle, 2022)
Hallux rigidus of the first metatarsophalangeal joint affects between 35% and 60% of the population over 65 years of age and has multiple treatment options, among which we highlight metatarsophalangeal arthrodesis and prosthesis. Regarding the arthroplasty technique, we aim to provide information on the characteristics of the material, model, and design and on which one offers better results, relating it to the characteristics of the patient, such as age, presence of inflammatory joint diseases, and viability and durability of the implant. Some studies on the clinical and functional results with different prosthesis models are briefly exposed. According to the AOFAS criteria, prosthesis and arthrodesis present similar effectiveness values and the decision of which technique to use will be determined considering several factors and characteristics previously exposed. CartivaTM is a synthetic polyvinyl alcohol hydrogel implant that has a water content with a compressive and tensile modulus similar to that of human articular cartilage. Thus, it is suitable for use in metatarsophalangeal hemiarthroplasties, and published studies in this regard report excellent short- and long-term clinical results. Level of Evidence V; Therapeutic Studies; Expert Opinion.